The Role Of Foreign Direct Investment In The Organization And Development Of An Innovation Cluster (Global Scientific Review, 2023)
The article examines the role and importance of creating innovative clusters in the socio-economic development of the country, the role and importance of foreign direct investment in the development of clusters, and discusses conclusions and recommendations based on international experience.